Factors associated with severe depressive symptoms among Chinese secondary school students in Hong Kong: a large cross-sectional survey - Doris Y. P. Leung; Sau Fong Leung; Xue-Lin Zhang; Jia-Yin Ruan; Wing-Fai Yeung; Yim-Wah Mak (Frontiers Media S.A., 2023)
BackgroundMany adolescents were reported to have severe depressive symptoms, and a careful assessment of its correlates is essential for prevention and intervention programs. This study aimed to gain insight into the prevalence of severe depressive symptoms and its association with factors at four levels (individual, relationship, school and society) in a large sample of Hong Kong Chinese secondary school students.MethodsSecondary school students from Secondary 1 through 7 were selected as participants using a cluster random sampling method. A questionnaire including inventories measuring 24 factors at the four levels (six individual factors, 11 relationship factors, three school factors, and four society factors) was completed by 8,963 participants (56.3% female) with a mean age of 15.1 (SD = 1.8) years. Students with a score of ≥15 on the Patient Health Questionnaire were defined as having severe depressive symptoms. The association between severe depressive symptoms and correlates were examined by t-test and χ2 test. Logistic regression models using a hierarchical approach then examined the individual contribution of these 24 factors to severe depressive symptoms with the control of other factors in the model.Results7.4% of the students have severe depressive symptoms. Twenty-two of the 24 factors were significantly associated with severe depressive symptoms in bivariate analyses. In the logistic regression, 11 factors (three individual factors: age, self-esteem and self-mastery; six relationship factors: tobacco use, alcohol drinking, drug use, paternal psychological control, dinner with parents, and perceived social support from friends; one school factor: felt pressure from homework; and one society factor: number of sibling) were statistically significant. Felt pressure from homework, alcohol drinking, and perceived social support from friends were the strongest correlates of severe depressive symptoms.ConclusionThe prevalence of self-reported severe depressive symptoms in Hong Kong Chinese secondary school students was high, and the identification of multiple associated factors at the four levels simultaneously provides a knowledge basis for the development of a comprehensive, multivariate model of factors influencing severe depressive symptoms in Chinese secondary school students. The factors identified in the present study may be helpful when designing and implementing preventive intervention programs.